ENDOSCOPIC MUCOSAL RESECTION TECHNIQUES FOR COLORECTAL POLYPS - Mandić, Olga (Medicinski podmladak, 2023)
Endoscopic mucosal resection (EMR) is an therapeutic technique developed for the resectioning sessile and flat lesions localized in the mucosa of any part of the gastrointestinal tract. It is easy to learn and allows the resection of large polyps that would otherwise require radical surgery. For the purpose of early detection of neoplasia of the gastrointestinal tract, the screening program for colorectal cancer proved to be the most important, and its wide acceptance led to a decrease in the incidence and mortality rate. This article reviews EMR techniques and focuses on large colorectal polyps, representing the most common indication for EMR. Before starting resection, the endoscopist should carefully and thoroughly examine the lesion and differentiate between resectable lesions and those potentially affected by the submucosal invasion. There are different methods of evaluating polyps; more recently advanced techniques are also used. The characteristics of colorectal lesions, including location, size, morphology, and histology, influence the choice of the optimal method of removal. EMR removes part of the wall of the colorectum that contains the mucosa, the muscularis mucosa and partially or completely, the submucosal layer. In addition to the removing benign adenomas of varying degrees of atypia, mucosectomy enables the treatment of early colorectal cancer where the risk of metastasis to the lymph glands is minimal. The primary goal of EMR is the complete and safe removal of colorectal lesion and the complete prevention of CRC. Techniques for performing EMR include conventional EMR with submucosal solution injection, hot loop, and electrocautery removal of colorectal lesions, as well as alternative EMR techniques such as cold loop EMR and “underwater” EMR. Major adverse events associated with EMR include bleeding and perforation after mucosectomy. Because of the risk of polyp recurrence regardless of the EMR technique, as well as the risk of metachronous polyps, control colonoscopies are necessary, especially in patients with the highest risk of recurrence.
Keywords: Colorectal polyps, optical diagnosis, endoscopic mucosal resection techniques, post-procedural bleeding and perforation